MASS BREEDING OF GRAM POD BORER, HELIOTHIS ARMIGERA (HUBNER) ON SEMI-SYNTHETIC DIET AND ITS BIOLOGICAL STUDIES - SHARMA, S. P.; GOEL, S. C.; SAINI, M. L. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1987)
The gram pod borer, H. armigera (Hb.) was reared on modified semi-synthetic diet developed by Nachiappan & Subramaniam (1974), in the laboratory. The caterpillars were successfully reared on this diet for 14 generations Further detailed studies on biology were conducted at constant temperature 26 - 1° C and 75 - 5% RH. The preoviposition and oviposition periods averaged 3.0 - 024 and 6.5 - 0 15 days, respectively. Average fecundity was 1145 - 6399 eggs per female. The lengevity for female and male was 16.50 - 1.35 and 11 10 - 1.49 days, respectively. The average incubation period was 3.85 - 0.36 days. The mean larval period was 16.30 - 167 days Pupal period for male and female was 14.85 - 0.16 and 12.89 - 0 20 days. Female produces heavier pupa compared to male.